Geburt umfassend betrachtet – Ansätze für ein Health Technology Assessment - Jonas, S. (Zeitschrift für ärztliche Fortbildung und Qualitätssicherung, Schwerpunktheft Geburtshilfe, Z. ärztl. fortbild. qual.sich. (ZaefQ), 2002)
Childbirth: A comprehensive perspective. Approaches to Health Technology Assessment. Are the routine interventions done during a normal birth in a hospital setting evidence based? The World Health Organisation worked out evidence based interventions especially for low risk women worldwide. The trained midwife is the most appropriate and cost effective caregiver in normal pregnancy and birth. Obstetrics in the area of conflict of technology, economy and law can turn a normal physiological event into a medical procedure. It leads to unnecessary interventions and to a concentration of a large numbers of labouring women in technically well equipped units with the concomitant costs. The technological advance run to the desire for perfectionism. In medical as well as in legal risk/benefit estimations different interests must be granted. The differences of payment of normal vaginal delivery and sectio are contradictory. Our handling of pregnant and birthing women shows their social value in the society. Health Technology Assessment adds to decision making by pointing out and analysing different aspects.